Konsep Perumusan Kaidah Nahwu Dalam Kitab Al-Iqtirah fi Ushul al-Nahwi Karya Imam Al-Suyuthi / Concept of Formulating Nahwu Rules in the Book of Al-Iqtirah fi Ushul al-Nahwi by Imam Al-Suyuthi - Alfikri Rausen Aditya; Sugeng Sugiyono (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
The book al-Iqtirah fi Ushul al-Nahwi by Imam Al-Suyuthi is one of the classic books that operates in the field of nahwu linguistics. In this book, Imam al-Suyuthi provides his concept of thinking regarding the postulates in determining and establishing a law in the science of Nahwu as well as the principles that must be considered when studying the science of Nahwu. This research aims to determine the concept of formulating the rules of nahwu in the book al-Iqtirah fi Ushul al-Nahwi by Imam Al-Suyuthi. The type of research used is qualitative research with a literature study approach. The data analysis technique in this research is content analysis. The results of this research found that Imam Jalaluddin Al-Suyuthi had a concept in formulating the rules of nahwu which departed from the opinions of previous scholars such as Ibn Jinni and al-Anbari. He believes that in formulating the rules of nahwu there are four propositions that can be used as a basis for thinking, namely samaa', ijmaa', qiyas, and istishab.Abstrak: Kitab al-Iqtirah fi Ushul al-Nahwi karya Imam Al-Suyuthi merupakan salah satu kitab klasik yang bergerak di bidang linguistik nahwu. Dalam kitab ini, Imam al-Suyuthi memberikan konsep berpikirnya mengenai dalil-dalil dalam menentukan dan menetapkan sebuah hukum dalam ilmu nahwu serta prinsip-prinsip yang harus diperhatikan dalam mempelajari ilmu Nahwu. Penelitian ini bertujuan untuk mengetahui konsep perumusan kaidah nahwu dalam kitab al-Iqtirah fi Ushul al-Nahwi karya Imam Al-Suyuthi. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi kepustakaan. Teknik analisis data pada penelitian ini yaitu content analisys (analisis isi). Adapun hasil dari penelitian ini ditemukan bahwa Imam Jalaluddin Al-Suyuthi memiliki konsep dalam perumusan kaidah nahwu yang berangkat dari pendapat ulama sebelumnya seperti Ibnu Jinni dan al-Anbari. Beliau berpendapat bahwa dalam merumuskan kaidah nahwu ada empat dalil yang bisa dijadikan sebagai landasan berpikir, yaitu samaa’, ijmaa’, qiyas, dan istishab.